2019
DOI: 10.1164/rccm.201807-1303le
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physiological Performance of Four Adaptive Servo Ventilation Devices in Patients with Complex Sleep Apnea

Abstract: NL, et al. E-cigarette use results in suppression of immune and inflammatory-response genes in nasal epithelial cells similar to cigarette smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Knitter et al previously attempted to describe MV differences between ASV-F and ASV-V devices in TECSA patients with preserved LVEF [ 4 ]. The latter study consisted of a randomized cross-over study comparing 4 devices (each used for one night only) and concluded that the ResMed S7 VPAP Adapt (an ASV-V device) was associated with a higher MV than ASV-F devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knitter et al previously attempted to describe MV differences between ASV-F and ASV-V devices in TECSA patients with preserved LVEF [ 4 ]. The latter study consisted of a randomized cross-over study comparing 4 devices (each used for one night only) and concluded that the ResMed S7 VPAP Adapt (an ASV-V device) was associated with a higher MV than ASV-F devices.…”
Section: Discussionmentioning
confidence: 99%
“…To limit this risk, a multicentre design without predefined ASV-rules or ASV-brand requirements was used. An important further limitation results from the impossibility of making direct comparisons between ASV-F and ASV-V. Because of our long-term design, it was impossible for us to deploy an independent pneumotachograph MV and therapeutic pressure measures, and we therefore used manufacturer software as in previous clinical publications [ 4 , 28 ]. However, based on the ASV bench-study published by Zhu et al [ 2 ], which used an independent pneumotachograph and demonstrated device-differences in MV and therapeutic pressures, one can assume that such machine related heterogeneity exists in real life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological studies suggest that algorithm might play a role. However, we do not have data to demonstrate that these acute physiological measurements translate into significant impact on outcomes [49].…”
Section: Challenges In Managing Csa/periodic Breathing In Chf With Rementioning
confidence: 86%
“…Some devices targeted a minute ventilation set at 90% of spontaneous ventilation to allow nocturnal PaCO 2 to increase slightly above the apnea threshold (3). Since their original design, options such as auto-titration of EPAP, of pressure support, and of back-up respiratory rate (BURR) have been added to the initial algorithms (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%